The impact of a dealer's failure on OTC derivatives market liquidity during volatile periods - Larry D. Wall; Ellis W. Tallman; Peter A. Abken (Federal Reserve Bank of Atlanta, 1996)
This paper develops a model in which information losses may be an important part of the cost of an OTC derivatives dealer's failure. A dealer failure forces solvent counterparties of a failed dealer to seek replacement hedges with other dealers. However, by forcing good firms into the derivatives market, the failure provides camouflage for insolvent firms seeking to speculate with a dealer that does not know their credit status. The paper models this information loss and uses the model to quantitatively evaluate a range of scenarios. The results suggest that a market breakdown is unlikely but not quite impossible.
Keywords: 330; Derivative securities; Liquidity (Economics)